Cotas fenomenológicas para el parámetro libre de la teoría Born-Infeld - Trejo Espinosa, María Anabel (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
In Chapter 2 of this thesis we will study the Born-Infeld theory, exemplifying the changes that produces in some systems. In Chapter 3 we will study the photon-photon dispersion in the QED. In Chapter 4 we will study the photon-photon dispersion in the Born-Infeld theory and we will give a quota for b, based on the experimental results of D. Bernard Et. to the. [11], where a height was obtained for the value of the dispersion effective section. The chapter 5 is intended to study the propagation of light within a field electromagnetic in both the QED and the Born-Infeld theory. In Chapters 6 and 7 we will study the photon splitting process in QED and in Born-Infeld theory, respectively, in chapter 7 we give a dimension for b assuming that the photon splitting process soon to be observed in Astrophysics.

En el capítulo 2 de esta tesis estudiaremos la teoría Born-Infeld, ejemplificando los cambios que produce en algunos sistemas. En el capítulo 3 estudiaremos la dispersión fotón-fotón en la QED. En el capítulo 4 estudiaremos la dispersión fotón-fotón en la teoría Born-Infeld y daremos una cota para b, basándonos en los resultados experimentales de D. Bernard et. al. [11], donde se obtuvo una cota para el valor de la sección eficaz de dispersión. El capítulo 5 tiene como propósito estudiar la propagación de la luz dentro de un campo electromagnético tanto en la QED como en la teoría Born-Infeld. En los capítulos 6 y 7 estudiaremos el proceso photon splitting en la QED y en la teoría Born-Infeld, respectivamente, en el capítulo 7 damos una cota para b suponiendo que el proceso photon splitting pronto será observado en la Astrofísica.
Instituto de Física y Matemáticas. Maestría en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-M-2011-0015; Electrodinámica; Lineal; Auto-energía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1158